Enhanced reduction of nitrobenzene derivatives using reusable Ni nanoparticles supported on multi-layered poly(1,2-phenylenediamine)-coated layered double hydroxides - Babamoradi, Jamshid; Ghorbani-Vaghei, Ramin; Alavinia, Sedigheh (Canadian journal of chemistry, 2022)
Recently, nanomaterials with layered double hydroxide (LDH) cores have been the subject of intense research regarding their promising applications in organic synthesis. In this study, nitrobenzene reduction is investigated by designing and synthesizing a novel LDH-based heterogeneous catalyst containing a nickel-1,2-phenylenediamine complex. The Cu–Zn–Al LDH was functionalized with copolymer bearing a glycidyl methacrylate (GMA) linkage that makes it suitable for grafting with 1,2-phenylenediamine. Overall, the synthesized LDH@MPS-GMA-PDA-Ni was found to be a highly efficient heterogeneous nanocatalyst that can catalyze nitroarene reduction with high yields under mild conditions.